Cultivating the Soul in Public Education: Internalizing Islamic Values Through School Culture to Construct Student Moral Character - Mohammad Iqbal; Ahmad Sukandar (CV. Media Digital Publikasi Indonesia, 2026)
In the midst of global moral decadence and the digital crisis affecting youth, the integration of religious values within public education has become a critical pedagogical imperative. This study investigates the processes, strategies, and impacts of internalizing Islamic values through school culture at SMP Negeri 3 Cianjur and SMP Negeri 4 Cianjur, Indonesia. Utilizing a qualitative case study approach with a descriptive-narrative design, data were gathered through participant observation, in-depth interviews, and documentation. The study analyzes how these public institutions transcend secular limitations by embedding religious praxis into the hidden curriculum. The findings reveal a multi-layered internalization strategy: (1) Uswah Hasanah (exemplary role modeling) by educators; (2) Structural habituation of rituals (congregational prayers, Quranic literacy); and (3) Environmental conditioning through Islamic-based regulations. The research concludes that the efficacy of moral formation relies not on dogmatic instruction, but on a symbiotic ecosystem involving school policy, teacher integrity, and parental synergy. These findings offer a reproducible model for value-based education in state-run schools facing modernization challenges.